Avaliando a promoção da saúde e prevenção do uso de drogas em ambiente escolar na perspectiva dos estudantes - Gomes, Tiago Cardoso (2015)
From the evidence of the current trend of increased consumption of alcohol and other drugs among adolescents, and the early start, it is necessary to carry out actions and preventive measures with students, and consider the school as educational environment favorable to their healthy development. The aim of the study was to evaluate the actions of promotion of health and prevention of drug use of a University Extension Project held a primary school in the perspective of the students. It conducted case study (focus group) to assess the actions of the Project and in addition, a cross-sectional study to describe the profile school, family and community participants. The site was the Municipal Elementary School SuzeteCuendet (EMEFSC), located in Vitória-ES, and the population students from 6th to 9th years of morning and evening shifts, and the participants included among those selected for the projectPrev-SchoolMultipliers in 2013. For data collection was used a structured questionnaire (closed and self fulfillment issues) and focus group. Data from cross-sectional study were tabulated and analyzed using the Statistical Package for the Social Sciences (SPSS 21.0) and, in turn, data from focus group (case study) were recorded, transcribed and worked for thematic analysis based on Bardin (2000). The actions of promotion of health and prevention of the use of Prev-SchoolMultipliers drugs were identified with fundamentals and principles of the models to prevent the use of alcohol and other drugs in the school environment, while the description of the profile of the participants identified variables that can be configured as factors related to the healthy development of children and adolescents. The evaluative perspective of the participants can contribute to better planning and implementation of new.